Quota Formula Review : Additional Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
In July, the Executive Board held its second formal discussion on the quota formula review. Directors agreed on the principles that should guide the review and the importance of meeting the January 2013 deadline, and there were indications of an emerging consensus in a few areas. However, views continued to diverge on several other key issues, and Directors stressed that completing the review will require a spirit of flexibility and compromise on all sides. This paper seeks to provide a basis for the next discussion, taking account of the views expressed in July. It begins by taking stock of the discussions to date. Based on this stock take, it seeks to highlight areas where a relatively broad consensus appears to be emerging. The paper also discusses possible options for addressing concerns raised about the openness variable and provides a range of simulations that seek to illustrate the effects of potential reforms to the formula. The simulations focus on those issues that have garnered the most attention in the discussions to date.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Emerging Market; GDP Blend; GDP; Open Economy; PP; Hong Kong Special Administrative Region, People's Republic of China